The Tape-Stripping Technique as a Method for Drug Quantification in Skin - Jose Juan Escobar-Chavez; V. Merino-Sanjuán; M. López-Cervantes; Z. Urban-Morlan; E. Piñón-Segundo; D. Quintanar-Guerrero; A. Ganem-Quintanar (Frontiers Media S.A., 2008)
Quantification of drugs within the skin is essential for topical and transdermal delivery research. Over the last two decades, horizontal sectioning, consisting of tape stripping throughout the stratum corneum, has become one of the traditional investigative techniques. Tape stripping of human stratum corneum is widely used as a method for studying the kinetics and penetration depth of drugs. This paper shows the applications of the tape stripping technique to quantify drug penetration through the skin, underlining its versatile application in the area of topical and transdermal drugs.